INOVASI PELAYANAN PUBLIK MELALUI APLIKASI PELAYANAN VIA ONLINE (PLAVON DUKCAPIL) OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIDOARJO - Sholicha, Irsy Kharimatus; Oktariyanda, Trenda Aktiva (Publika, 2023)
Public service is a necessary component of maintaining a government system that is responsive to community requests. However, there are still complaints from the public concerning government services, one of which is population administration in Sidoarjo Regency. The bigger the population, the greater the need for population management. As a result, the government of the Sidoarjo Regency launched an online service application service innovation (Plavon Dukcapil). The intention goals to make it easier for the public to receive population administration management services through the online Plavon Dukcapil website. The purpose of this research is to discuss Disdukcapil Sidoarjo's creation, Plavon Dukcapil. The qualitative descriptive research method was used in this study. The theory used for this study is the characteristics of e-government innovation by Rokhman, Ali (2011) which consists of 5 (five) indicators, namely relative advantage, image, compatibility level, ease of use, and intensity of use. Data collection methods include observation, interviews, and documentation. Disdukcapil Sidoarjo, who manages the dukcapil platform innovation program, and members of the community who use the service were interviewed. According to the study's conclusions, the Sidoarjo Regency Government did great work in establishing the Plavon Dukcapil service innovation. The results of the analysis using the indicators of e-government innovative characteristics are suitable; however, there are still issues in the website service system due to multiple obstacles encountered, such as website errors. So the greatest advice is to improve the Plavon Dukcapil website's performance system so that the services provided may be maximized. Keywords: Innovation, Service, e-government, Plavon Dukcapil, Population Administration.